The role of pre-existing faults in the early–middle eocene palaeogeographic evolution of the PY4 sag, Pearl River Mouth basin, South China Sea - Guo, Wei; Peng, Guangrong; Chen, Zhaoming; Zheng, Xiongwei; Wu, Jing; He, Jinhai (Marine and petroleum geology, 2024)
The early–middle Eocene represents a pivotal geological phase in the Pearl River Mouth Basin, as it witnessed the emergence and transformation of numerous Cenozoic rifted basins. Nonetheless, the research on the palaeogeography of this period and its interplay with pre-existing faults within the pre-Cenozoic basement remains scant. This article delves into this topic through the lens of the PY4 Sag, a prominent ENE-striking rifted basin situated in the central region of the basin. Initially, we reconstruct the palaeogeography of five third-order sequences within the study interval, using 3D seismic data and drilling data. Then, by amalgamating characteristics of pre-existing faults in the pre-Cenozoic basement, garnered from the published literature, and analyzing their Cenozoic evolution and influence on lake basin structure, sedimentary environment, and sediment distribution, we delve into the correlation between these pre-existing faults and the stratigraphic palaeogeographic evolution in the study area. Our findings reveal that the PY4 Sag experienced five distinct stages of palaeogeographic evolution from the early to middle Eocene, including the initial formation of an ultradeep lake (SQ1), filling of an ultradeep lake (SQ2), early expansion of a shallow lake (SQ3), late expansion of a shallow lake (SQ4), and expansion of a semideep lake (SQ5). This process was accompanied by a gradual migration of the subsidence and sedimentation center of the lake basin from northeast to southwest. Since the Cenozoic, influenced by northwest extension and its clockwise rotation, two pre-existing thrust fault systems striking ENE and EW–WNW within the basement of the Pearl River Mouth Basin have been successively activated. This led to the emergence of numerous ENE-striking normal faults (exhibiting relatively stronger activity) during the early Eocene (SQ1) and EW–WNW-striking normal faults (mainly distributed in the west of the study area) during the middle–late Eocene. Consequently, the PY4 Sag developed a deep and expansive ENE-striking lake basin in the early Eocene, followed by the formation of several smaller EW–WNW-striking lake basins in the middle–late Eocene. The early ENE-striking deep lake progressively evolved into a shallow one due to continuous filling, while the later E–W-striking lake basins broadened and deepened, culminating in the amalgamation of these two distinctively oriented lake basins. In essence, the different spatio-temporal evolution of these two basement pre-existing fault systems during the Eocene, together with episodic magma intrusions in the middle Eocene, are the primary factors controlling the palaeogeographic evolution in the PY4 Sag. Analogously, other ENE-striking sags within the Zhu I Subbasin of the Pearl River Mouth Basin underwent a comparable palaeogeographic transformation during the early–middle Eocene. •The early–middle Eocene palaeogeography of the PY4 Sag is reconstructed first time.•The early–middle Eocene PY4 Sag experiences palaeogeographic evolution from ultradeep lake to shallow–semideep lake.•The relationship between pre-existing faults and palaeogeographic evolution of rifted basins is discussed.•Different evolution of pre-existing faults and magma intrusions control palaeogeographic of the PY4 Sag.•A palaeogeographic evolution model for ENE-striking depressions in the Pearl River Mouth Basin is established.